The Role of Point-of-Care Test to Control Highly Pathogenic Avian Influenza in Indonesia - Simson Tarigan (Indonesian Center for Animal Research and Development, 2016)
Rapid diagnosis followed by stamping out protocol has proven to be the most effective means of eradication of Highly Pathogenic Avian Influenza (HPAI) H5N1. The standard of AI tests are PCR and virus isolation, however their results often take times to initiate rapid eradication protocol. For that reason, a point-of-care (POC) test which is a rapid test used at the location of outbreak (where mortality and morbidity of poultry occur), to help field officer for identification of AI. This paper describes several techniques for detection of HPAI H5N1 virus, POC test and principal mechanism of lateral flow immunoassay which has been generally used in POC test. At present, POC test for HPAI H5N1 rather low sensitivity and expensive, therefore, further research is needed to improve its sensitivity of the tool.